2005
DOI: 10.4319/lo.2005.50.4.1049
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation in the δ15 N and δ13 C of coral tissue and zooxanthellae in Montastraea faveolata collected from the Florida reef tract

Abstract: Tissues were collected from Montastraea faveolata at five locations on the Florida Reef tract representing both nearshore and offshore environments. The tissue and zooxanthellae were removed from the skeletons, separated, and subsequently analyzed for ␦ 15 N and ␦ 13C. The mean ␦ 15N value in the coral tissue was ϩ6.6 (Ϯ0.6‰) while the ␦ 13 C was Ϫ13.3 (Ϯ0.5‰) (n ϭ 197). The ␦ 15 N and ␦ 13 C of the zooxanthellae were ϩ4.7 (Ϯ1.1‰) and Ϫ12.2 (Ϯ1.0‰), respectively (n ϭ 147). The differences in the ␦ 15 N and ␦ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
73
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 34 publications
10
73
2
Order By: Relevance
“…Changes in δ 15 N of anthozoan and algal tissue are regularly used to track nitrogen sources in these organisms [see discussion by Swart et al (Swart et al, 2005)]. In the present study, the largest change was observed in the symbionts (−4‰), which are the main site of ammonium assimilation (Grover et al, 2002;Pernice et al, 2012).…”
Section: Discussionsupporting
confidence: 53%
“…Changes in δ 15 N of anthozoan and algal tissue are regularly used to track nitrogen sources in these organisms [see discussion by Swart et al (Swart et al, 2005)]. In the present study, the largest change was observed in the symbionts (−4‰), which are the main site of ammonium assimilation (Grover et al, 2002;Pernice et al, 2012).…”
Section: Discussionsupporting
confidence: 53%
“…These values are relatively low compared to other zooxanthellate coral species, which mostly range between -12 and -14 ‰ at the same depths (Muscatine et al 1989, Swart et al 2005, Alamaru et al 2009a), but similar values have been previously reported for M. auretenra (Muscatine et al 1989). Lower δ 13 C values can hint at lower photosynthesis and/or at faster replenishment of internal DIC from ambient seawater DIC due to reduced diffusion distances.…”
Section: Diffusion Constraintsmentioning
confidence: 65%
“…3-4% indicate land-based nutrient pollution (Lapointe et al 2004). In the same region, however Swart et al (2005) found no clear signals in coral d 15 N from offshore to nearshore reefs but did find significant temporal variation, suggesting seasonal changes in the relative importance of coral autotrophy and heterotrophy.…”
mentioning
confidence: 80%
“…With the use of discernable differences between d 15 N values for natural versus anthropogenic sources of nitrogen, a number of studies have investigated nitrogen pollution in coral reef environments via measurement of tissue d 15 N in benthic organisms (e.g., Sammarco et al 1999;Heikoop et al 2000;Swart et al 2005). Recognition of an isotopic signal from anthropogenic nitrogen in benthic organisms depends on clear differentiation of d 15 N in potential sources.…”
mentioning
confidence: 99%